The Appointment Of Project Consultant In Green Construction Projects: A Proper Framework - Shariffuddin, Nadia Alina Amir (2017)
This research focuses on exploring project consultants’ appointment practices in green construction projects by highlighting the processes and procedures, selection criteria as well as challenges in the issue. The adaptation of the Open System Theory will showcase the relationship between each aspect in appointment practices. Using the qualitative method, a two-stage approach is adopted, i.e. Tier-1 and Tier-2 studies. Tier-1 acts as a preliminary study, whereas Tier-2 is an in-depth study. It is discovered that there are two procedures that can be taken to appoint a project consultant; either through appointment by the client, or by the architect.